Environmentally benign and biocompatible CuO@Si core-shell nanoparticles: As electrochemical l-cysteine sensor, antibacterial and anti-lung cancer agents. Issue 6 (15th March 2023) - Gowtham, S.M.; Dhivya, R.; Muthulakshmi, L.; Sureshkumar, S.; Ashraf, M.; Pandi, M.; Mayandi, J.; Annaraj, J.; Sagadevan, Suresh
Abstract: CuO and CuO@Si core-shell nanoparticles were synthesized by hydrothermal method and analyzed their structural, chemical and morphological properties using XRD, FESEM, TEM, UV–Vis, FT-IR, and BET analysis. CuO and CuO@Si core-shell nanoparticles are appeared as spherical and homogeneous in size, with respective diameters of 17 and 80 nm in FE-SEM analysis. This developed nanomaterial was used to modify the electrode and as an efficient electrochemical strategic tool for the trace-level detection of l -cysteine. The cyclic voltammetry (CV), differential pulse voltammetry (DPV), and amperometry studies indicated that the CuO@Si core-shell nanoparticles show remarkable sensitivity for l -cysteine. The modified glassy carbon electrode shows linearity with the addition of increasing concentration (20–240 μL) of l -cysteine addition, which yields the detection limit of 0.015 μM. The CuO@SiO2 core-shell nanoparticle is simple, rapidly synthesized, reliable, and the adopted synthetic method did not require extensive sample treatment. These nanomaterials have been utilized as potential anticancer agents against A549 & HEK 293 cell lines based on their MTT assay observations. The obtained antibacterial and anticancer properties have demonstrated that they are remarkably potent to inhibit bacterial growth, induce effective apoptosis in cancer cells relative to healthy cells, and also their environmental safety.